Attitude towards contract farming among Malaysian agriculture learning institution students - Abu Samah, Bahaman; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Uli, Jegak (Science Publications, 2010)
Problem statement: The government’s effort in enhancing agriculture productivity cannot be argued. The introduction of contract farming is one of the ways. Contract farming includes a number of new agriculture activities such as leech rearing, worm rearing, vanilla farming, herbs, catfish and many more. However, is the youth who are the pillar of this industry have a positive attitude towards it? This was the main objective of this study, to investigate the attitude of Malaysian agriculture institution students toward contract farming and factors that affect it. Approach: This was a quantitative study and data was gathered through a survey questionnaire. A total of 194 respondents from two main agriculture learning institutions in Malaysia were selected through a simple random sampling. The data collection took almost two months to be completed. Results: As expected, the study revealed that the Malaysian agriculture institution students have a high level of attitude towards contract farming. Further analysis through multiple regression analysis informed us that three factors which are acceptance, support and knowledge are significant predictors of youths’ attitude towards contract farming. Conclusion: In order to enhance the attitude of youth towards contract farming, exposure to contract farming among the youth should be doubled and a specific course on contract farming can be introduced. Besides, establishing contract farming youth club can be introduced.